Hukum Agraria Dalam Penyelesaian Sengketa Tanah Di Indonesia - Rio Rolando; Santy Fitnawati Wn; Dwi Juniyanto; Nahes Setiawan (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Agrarian law is the entire norm legal norms, whether written or notwriting that regulates legal relations between legal subjects in the agrarian sector. SeciIn human life, land has a very important role because in reality will be in touch during the length of time between humans and the land. In this case it can It is described that the relationship between humans and land is very close because land is m human livelihood. However, in reality there are still many people who take advantage of it conditions where there are weaknesses in law enforcement resulting in an increase in a number of land disputes. Land disputes are unavoidable in this day and age, besides dise This is because weak law enforcement officers are also caused by various reasons The need for land is very high nowadays while the number of plots of land is limited. In resolving land disputes there are several settlement processes can This can be done, among other things, through court and mediation.